ESTUDO DE RISCO CARDIOVASCULAR: UMA PROPOSTA DE USO DA MIELOPEROXIDASE SÉRICA E AVALIAÇÃO DE PRESSÃO INTRACRANIANA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2017)
The Acute Coronary Syndrome (ACS) defines a range of clinical changes that are compatible with myocardial ischemia, resulting in the death of myocardial cells due functional deficit of blood flow, characterizing the acute myocardial infarction (AMI). The AMI is evidenced through clinical data that are reinforced by electrocardiogram (ECG), imaging and even the biochemical markers (biomarkers) evaluation, such as serum creatine phosphokinase (CK), its isoenzyme MB fraction (CK-MB), troponin and new biomarkers not yet included in routine laboratory tests, such as myeloperoxidase (MPO). In addition to new laboratory markers, science allows the development of new technologies for clinical assessment of patients, providing new information and less risk, such as non-invasive evaluation of intracranial pressure (ICP). This study is justified by the need to predict earlier the complications in patients with suspected AMI, as well as evaluate them as to the diagnosis and prognosis of the event in question. Thus, we sought to study patients with suspected ACS/AMI about the cardiovascular risk and possible PIC change through traditional biomarkers, most current markers ( "gold standard") and new biomarkers and new ICP monitoring technology. Therefore, from a population of 20 patients, randomly selected according to gender and age, separated into two groups: CK-MB≥25 IU (n = 6) and CK-MB<25 IU (n = 14), which were submitted to measurement of PIC and PAS, as well as biochemical and hematological measurements, and specific cardiac biomarkers. As a result, there was correlation of clinical significance between the values of creatine kinase MB fraction (CK-MB) and glycated hemoglobin (HGBA1C). From these data, it started to study two cases that were selected two patients. It was observed that even with changes of CK-MB, troponin and myeloperoxidase (compared to laboratory practice reference values for traditional markers and "gold standard" and MPO value considered normal in the literature), it was found not manifestations that have allowed to observe reduction of cerebral compliance, where the waves P2 are larger than P1, and therefore, there were no PIC changes identified for patients under the conditions studied. Thus, it was concluded that, even without demonstration of PIC change in this work, it is not possible to exclude the value of its inclusion in the clinical evaluation, considering that biases, like the sample universe and the time of collection of PIC or the use of medication at the admission time on hospital, may have contributed to the non-registration of changes in ICP, even in cases where patients had an unfavorable evolution of the clinical picture.
Keywords: pressão intracraniana; infarto agudo de miocárdio; intracranial pressure; acute myocardial infarction; cardiac biomarkers; CNPQ::CIENCIAS DA SAUDE::MEDICINA